La función del tutor en la estrategia de Aprendizaje Basado en Problemas en la formación médica en la Facultad de Medicina de la Universidad de Antioquia (2012)
ABSTRACT: In the context of the curricular renewal undertaken since 2000, the Faculty of Medicine (University of Antioquia, Medellín, Colombia) has implemented the teaching strategy ProblemBased Learning (PBL). This article discusses the role of PBL tutors, teacher training and the perception of students and teachers on the performance of tutors. The study is part of a larger qualitative study aimed at evaluating the impact of PBL on medical curriculum at this institution. A triangulation of sources was used. They were: data provided by PBL participants (students, tutors and coordinators), analysis of articles about the strategy written by teachers of this Faculty and information obtained from experts in the topic. It was found that PBL has stimulated the adoption of new roles amoung teachers, and that students are satisfied with this way of learning and interacting with teachers. However, there are still weaknesses in PBL training among teachers, which generate inconsistencies in the development of the strategy. It is recommended to broaden and deepen teacher training in order to strengthen the role of tutors in PBL, as well as to establish common spaces to share practices and discourses.